Pelatihan Bahasa Inggris Untuk Siswa-Siswi di TK Melati Indah Sayang-Sayang Cakranegara Mataram - Kamarudin, Kamarudin; Tawali, Tawali (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
Community service is the implementation of knowledge gained in schools, or lecturing process formally or informally. This community service aimed at giving English language training towards students of TK Melati Indah Sayang-Sayang, Cakranegara Mataram. This community service used lecturing, practice, and discussion. The respondents consisted of 30 students. The result of the training concluded that English language training towards students of TK Melati Indah Sayang-Sayang, Cakranegara Mataram was successful. It is proved from the students’ enthusiasm within the process of the training and their learning achievement after giving the training. Thus, the training of English language to the students is highly important especially in TK Melati Indah Sayang-Sayang as they will be the agent of change and future generation who will acquire English language well. Through this training, students of TK Melati Indah Sayang-Sayang are expected to have knowledge and basic experience to communicate through English language as their foundation and motivation to develop their skill.